2008
DOI: 10.4025/actascianimsci.v24i0.2336
|View full text |Cite
|
Sign up to set email alerts
|

Uso da parafina incorporada à cera alveolada em colônias de abelhas <em>Apis mellifera</em> L. africanizadas para produção de mel

Abstract: RESUMO.O objetivo foi avaliar favos construídos a partir de três tratamentos, lâminas de cera alveolada, lâminas de cera alveolada com parafina e parte do quadro sem cera. Foram utilizadas dez colônias de abelhas africanizadas, Apis mellifera L. (Hymenoptera, Apidae) existentes na região de Marialva, Estado do Paraná. Foram efetuados mapeamentos da área construída e ocupada com mel, a intervalos de aproximadamente 20 dias. Três quadros, cada um contendo os três tratamentos foram colocados nas posições lateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…FTIR spectroscopy is generally well-recognized as very reliable or promising method in analysis of various food systems (such as honey, milk, olive oil, juice, etc.) for authentication purposes (Casale & Simonetti, 2014;Cozzolino, Corbella, & Smyth, 2011;Karoui, Downey, & Blecker, 2010;Rios-Corripio, Rojas-L opez, & Delgado-Macuil, 2012), and even more demanding systems such as those involved in forensic sciences (Yu & Butler, 2015). However, it was not used for the authentication of beeswax until the second decade of this century.…”
Section: Disadvantagesmentioning
confidence: 99%
See 1 more Smart Citation
“…FTIR spectroscopy is generally well-recognized as very reliable or promising method in analysis of various food systems (such as honey, milk, olive oil, juice, etc.) for authentication purposes (Casale & Simonetti, 2014;Cozzolino, Corbella, & Smyth, 2011;Karoui, Downey, & Blecker, 2010;Rios-Corripio, Rojas-L opez, & Delgado-Macuil, 2012), and even more demanding systems such as those involved in forensic sciences (Yu & Butler, 2015). However, it was not used for the authentication of beeswax until the second decade of this century.…”
Section: Disadvantagesmentioning
confidence: 99%
“…Field studies on the acceptance or rejection of adulterated comb foundation by the honey bee colony are scarce (Castro, Medici, Sarlo, & Eguaras, 2010;Darchen & Lavie, 1958;Medici, Castro, Sarlo, Marioli, & Eguaras, 2012;Ribeiro da Silva, Ribeiro, Toledo, & Toledo, 2002;Semkiw & Skubida, 2013;Toledo, 1991). As reported in several studies Serra Bonveh ı & Orantes Bermejo, 2012;, comb foundation without any adulterants are rare and most contain 5-20% of paraffin.…”
Section: Investigating Brood Survival On Adulterated Comb Foundationsmentioning
confidence: 99%
“…Da Silva et al (2002) suggested a possibility of using a paraffin-adulterated wax foundation for formation of combs used in honey supers; however, such combs were best accepted by bees in the honey super center. Studies showing no negative effect of paraffin adulteration on brood survival may encourage using this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…These spatial distribution patterns may be related to the ecological preferences of the species, as influenced by specific types of microenvironments for reproduction and search for food resources (FERREIRA; SANTOS, 2016;SILVA et al, 2002).…”
Section: Discussionmentioning
confidence: 99%